A model-driven approach for collaborative service-oriented architecture design - Touzi, Jihed; Benaben, Fréderick; Pingaud, Hervé; Lorré, Jean Pierre (International journal of production economics, 2009)
In a collaborative context, the integration of industrial partners deeply depends on the ability to use a collaborative architecture to interact efficiently. In this paper, we propose to tackle this point according to the fact that partners of the collaboration respect the Service-Oriented Architecture (SOA) paradigm. We propose to design such a collaborative architecture according to Model-Driven Architecture (MDA) principles. We aim at using business models to design a logical model of a solution (logical architecture) as a principal step to reach the final collaborative solution. This paper presents the theoretical aspects of this subject and the dedicated transformation rules.